Tinkering : kids learn by making stuff - Gabrielson, Curt, ....- (San Francisco : Maker Media, 2015)
How can you consistently pull off hands-on tinkering with kids? How do you deal with questions that you can't answer? How do you know if tinkering kids are learning anything or not? Is there a line between fooling around with real stuff and learning? The idea of learning through tinkering is not so radical. From the dawn of time, whenever humanity has wanted to know more, we have achieved it most effectively by getting our hands dirty and making careful observations of real stuff. Make: Tinkering (Kids Learn by Making Stuff) lets you discover how, why--and even what it is--to tinker and tinker well. Author Curt Gabrielson draws on more than 20 years of experience doing hands-on science to facilitate tinkering: learning science while fooling around with real things.
Keywords: Science -- Juvenile literature; Science -- Experiments -- Juvenile literature